Design, synthesis, and antibacterial activity of N-(trifluoromethyl)phenyl substituted pyrazole derivatives. Issue 10 (27th August 2021) - Saleh, Ibrahim; Raj KC, Hansa; Roy, Subrata; Abugazleh, Mohd Kotaiba; Ali, Hashim; Gilmore, David; Alam, Mohammad A.
Abstract : Design and synthesis of N -(trifluoromethyl)phenyl substituted pyrazole derivatives and their potency as antimicrobial agents are described. Abstract : Design and synthesis of N -(trifluoromethyl)phenyl substituted pyrazole derivatives and their potency as antimicrobial agents are described. Several of these novel compounds are effective growth inhibitors of antibiotic-resistant Gram-positive bacteria and prevent the development of biofilms by methicillin-resistant Staphylococcus aureus (MRSA) and Enterococcus faecalis . These compounds eradicated the preformed biofilms effectively and were found to be more effective than the control antibiotic vancomycin. Potent compounds showed low toxicity to cultured human embryonic kidney cells with a selectivity factor of >20. The most promising compound is very potent against meropenem, oxacillin, and vancomycin-resistant clinical isolates of Enterococcus faecium . Investigations into the mode of action by performing macromolecular synthesis inhibition studies showed a broad range of inhibitory effects, suggesting targets that have a global effect on bacterial cell function.